Implementation of The AHP And MOORA Methods For Admission Selection of Stmik Lecturers Syaikh Zainuddin NW - Lalu Puji Indra Kharisma; Muh. Fahrurrozi; I Gede Iwan Sudipa (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2021)
STMIK Syaikh Zainuddin NW Anjani always strives to improve quality or internal quality sustainably as a strategy to be able to compete with other universities. The institution itself realizes that to achieve educational goals and maintain the quality of education and produce good outputs, it requires commitment, strategies, appropriate methods, and adequate human resources in the process of achieving it. One way to improve the quality of a university is to select teaching staff or lecturers because the quality of lecturers will greatly determine the high and low quality of a university. Based on the problems that arise, a decision support system is needed that can handle the influence relationship between parameters for the selection process for lecturer acceptance. In this study, the Analytical Hierarchy Process (AHP) method and the Multi-Objective Optimization on the Basis of Ratio Analysis (MOORA) method were used to determine alternative priorities for prospective lecturers. The AHP method is used to determine the weight of the criteria, sub-criteria, and scoring data, while the MOORA method is used to calculate the final score and ranking.